Template based procedural rigging of quadrupeds with custom manipulators - Bhatti, Zeeshan; Shah, Asadullah; Waqas, Ahmad; Malik, Hafiz Abid Mahmood (2013)
Character rigging is a process of endowing a character with a set of custom manipulators and controls making it easy to animate by the animators. These controls consists of simple joints, handles, or even separate characters selection windows. This research paper present an automated rigging system for quadruped characters with customs control and manipulators for animation. The full character rigging mechanism is procedurally driven based on various principles and requirements used by the riggers and animators. The automation is achieved initially by creating widget then can be customized by the rigger according to the character shape, height and proportion. Then joint locations for each body parts are calculated and widgets are replaced programmatically. Finally a complete and fully operational procedural generated character control rig is created and attached with the underlying skeleton joints. The functionality and feasibility of the rig was analyzed from various sources and actual character motion and a requirements criterion was met. The final rigged character provides an efficient and easy to manipulate control rig with no lagging and at high frame rate.